Reforming port processes in India for logistics efficiency. - Mitra, Sabyasachi; Banerjee, Pritam; Sanganeria, Atul (ADB briefs., 2021)
This brief offers policy recommendations for streamlining and digitizing port logistics and operations in India based on findings of a study conducted on the Jawaharlal Nehru and Vishakhapatnam ports.